Managing Ethno-Nationalism within Special Territorial Autonomy Policy: Comparative Cases between Aceh and Papua - Jati, Wasisto Raharjo (Jurnal Politik, 2023)
The implementation of special autonomy regions is how the central government acknowledges the uniqueness and significant contributions of specific regions to Indonesia. The acknowledgment is then accommodated within special autonomy policies. Starting with Papua in 2001, there are eight provinces with special regions. Despite having a special autonomy status, those provinces may have more problems. The issues are mainly the historical root of integration with Indonesia, resource inequality, and the genuine representations of indigenous people as officeholders. These three issues have been common problems in Indonesia since the up-and-down relationship exists between the central government and those special autonomous regions. The unequal compensation in revenue transfer always becomes a hotbed that recalls the integration process with Indonesia long ago. In line with the previously mentioned problems, this paper aims to evaluate the policy performance of special autonomy policies in Aceh and Papua. Both regions are worth investigating because there are always disputed classical problems that disrupt national integrity. Most importantly, both regions have insurgency movements that force the central government to respond swiftly. Compared with other special autonomous regions, Aceh and Papua have been in a turbulent position with Jakarta for many decades. These fluctuating relationships show unresolved problems that are still ingrained in both regions. Following up on the mentioned problems briefly, this paper reveals that while special autonomy in Aceh technically has ended the long conflict, Papua still struggles with scattered conflict in some regions. These different results show the remaining challenges the special autonomy policy should deal with very soon.